Evidence of health impairment of Megapitaria squalida (Bivalvia: Veneridae) near the hot spot of a mining port, Gulf of California - Yee-Duarte, Josué Alonso; Ceballos-Vázquez, Bertha Patricia; Shumilin, Evgueni; Kidd, Karen; Arellano-Martínez, Marcial (HIDROBIOLÓGICA, 2018)
It is known that organisms inhabiting polluted marine habitats may experience adverse physiological effects. The port of Santa Rosalía, Gulf of California, is characterized by high concentrations of heavy metals in sediments, particularly Cu, Zn, Co, Mn, Pb, and U, which are potentially toxic to the marine biota. In addition, this port receives urban wastewater that contributes mostly organic pollutants to the coastal zone. Goals. The main objective of this work was to determine whether clams in the mining region showed adverse effects because of the contamination. Methods. Through the analysis of biometric parameters, condition index, and weight-length relationship, the overall health of the chocolate clam Megapitaria squalida was evaluated in the coastal zone of the Santa Rosalía port and compared with data for clams from four mining-free areas. Results. Our findings revealed that clams from Santa Rosalía showed poor health, evidenced by their smaller size, inferior condition, and negative allometric growth compared to clams from all other sites, including San Lucas, a site located a few kilometers away from the pollution hot-spot and where the conditions of temperature and food availability are similar to those in the port area. Conclusions. All of the above suggests negative physiological effects in this species possibly caused by contamination from metals and/or organic pollutants from urban discharges. Particularly, it is likely that M. squalida at the mining site allocates more energy towards depurating or storing metals, in turn leading to poorer condition and deficient growth.